Bentuk-Bentuk Konstruksi Identitas Postkolonial dalam Novel Tenggelamnya Kapal Van der Wijck - Bangbang Yogie Wijaya; Diyanah Nisa Halimatussadiah (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2020)
Postcolonial becomes an interesting topic to be discussed when it has changed the custom and cultural order that had existed in the previous community. Postcolonialism received many pros and cons comments, one of which was delivered by HAMKA in its pro-work entitled The Sinking of the Van der Wijck Ship. Through the postcolonial study of Homi K. Bhabha, the author examines the forms of identity construction conveyed by HAMKA in his novel. This research uses descriptive qualitative method to look for characteristics, elements, traits or phenomena.